SPEEDING UP JUSTICE: A CRITICAL ANALYSIS OF THE PRINCIPLE OF SPEEDY, SIMPLE, AND LOW-COST TRIALS IN INDONESIAN CORRUPTION CASES - Ridwan, Ridwan; Mega Jaya, Belardo Prasetya; Jaya, Arizon Mega; Octavian, Ryan (Kanun Jurnal Ilmu Hukum, 2024)
This article investigates the issue of delays in law enforcement's implementation of criminal law in corruption cases, particularly in relation to the principles of speedy, simple, and low-cost trials. Utilizing a normative legal method and statutory approach, alongside case studies, the study explores the persistent delays in the Indonesian criminal justice system despite the emphasis on these principles. Delays in the reading of indictments have raised suspicions and potential discrimination in the enforcement of corruption cases. The right of a defendant to a prompt resolution, as outlined in the Criminal Procedure Code aligning with the shift from an inquisitorial to accusatorial principle and human rights development, is highlighted. However, the findings reveal that these principles are not consistently and effectively applied in Indonesia's criminal justice system. Key issues identified include prolonged, complex, and costly law enforcement processes in corruption cases, as well as obstacles hindering the swift and cost-effective resolution of state losses. Discriminatory practices, though not overt, manifest in various stages of the legal process, impeding the realization of fast, simple, and low-cost justice. To address these challenges and ensure fair trials, law enforcement must prioritize ethical and moral considerations in their practices